Arsitektur Masa Pandemi: Ruang Keempat Sebagai Pemaknaan Ruang-Ruang Pada Rumah Tinggal - Siti Sujatini; Euis Puspita Dewi (Universitas Persada Indonesia YAI, 2021)
The recommendation the government to residents are, school and do other activities athome (work / school from home) has caused high frequency in settlement or housesactivities. An increase in the frequency of activities with different kinds of the nature andtype of activity in dwelling in the pandemic that has caused many changes of the meaningsand functions of occupancy rooms. Occupancy very important besides serves as theresidence also serves to do all activities due to exertion out occupancy is not currentlyallows. This report is in order to know how far the meaning change and functions of spaceon occupancy so that this research result can be used as a reference to the designers indesigning home lives in accordance with the needs now. Methods used is the explorationand identification and grouping the activities that occurs in some dwelling houses, spacesthen identification used for the activities of usually accomplished outdoors, diketahui mixing and will be of various types place, first place, two and third place, wherecombination some place typologies meaning as an activity to the fourth space. The resultobtained is that the presence of the third and fourth not prolong the problem but in fact theoccurrence of the fourth of this to solve problems and the presence of the fourth was notjust for improving the economy but also for safety sake, health and comfort